A New Exceptionally Preserved Cambrian Priapulid from the Chengjiang Lagerstätte. (March 2014) - Ma, Xiaoya; Aldridge, Richard J.; Siveter, David J.; Siveter, Derek J.; Hou, Xianguang; Edgecombe, Gregory D.
Abstract : A fossil priapulid, Eximipriapulus globocaudatus new genus new species, is described from the Cambrian Chengjiang Lagerstätte of Yunnan, China. The exceptional preservation of the animal reveals morphological details that allow direct comparison with extant priapulids. The body is divisible into a partially eversible pharynx, a smooth collar, a scalid-bearing introvert, a neck with triangular scalids, an unsegmented trunk with annulations, and a distinctly expanded terminal region. Several specialized regions of the alimentary canal are recognized: a pharynx (lined by cuticle and bearing teeth), esophagus, midgut, hindgut, and a terminal anus. The sample includes a putative juvenile. The animal is inferred to have been an active burrower using a double-anchor strategy, practicing both deposit feeding and carnivory. Inclusion of Eximipriapulus in the most recent character matrix for cladistic analysis of fossil and Recent priapulids resolves the new genus within the priapulid crown group.